Dampak Motivasi Terhadap Peningkatan Kinerja Individu - Adie Erar Yusuf (Humaniora, 2014)
Individual’s performance is influenced by various factors, as: motivation, competency, environment, and technology. High working motivation is expected to improve performance in the organization. It needs various planned and systematic techniques to improve the motivation to be effective. Based on motivation theories, motivation is the underlying reason for an individual to do something. Individuals who have high motivation might mean that they have reasonable cause to achieve the expected performance. In contrast, individuals with low motivation certainly cannot contribute optimally for towards their performance.